Anti-money laundering and combating the financing of terrorism compliance: Are FATF member states just scratching the surface? - Mekpor, E.S. (Journal of Money Laundering Control, 2019)
Purpose – The purpose of this paper is to investigate how well countries comply with global anti-money laundering and counter-financing of terrorism (AML/CFT) regulations. Design/methodology/approach – With the help of an AML/CFT compliance index composed by the author, this study is able to numerically quantify countries’ AML/CFT compliance levels. Countries were selected based on their membership with the Financial Action Task Force (FATF), precisely members who have gone through at least one round mutual evaluation and have duly submitted a report to the task force. The AML/CFT index was composed by assigning numeric values to the individual country ratings across all 49 FATF recommendations contained in their mutual evaluation reports (MER). Findings – Some notable findings include the yearly global level of AML/CFT compliance between the period 2004 and 2016, as well as compliance levels across continents for the same period. Compliance levels for the seven components of the FATF recommendations were also reported to help assess which set of recommendations countries comply with the most and why they do. It was also found that countries’ lack of compliance was as a result of high cost of compliance with FATF recommendations. Research limitations/implications – The main limitation of this study was a lack of high-frequency AML data of countries, especially less-developed countries. Originality/value – The uniqueness of this paper lies in the fact that the AML/CFT compliance index constructed and used in the study is the first of its kind.
Research Article
Keywords: Money laundering